2010
DOI: 10.1080/15374411003691701
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Anxiety Symptoms in Preschool-Aged Children: The Revised Preschool Anxiety Scale

Abstract: The purpose of this study was to test the validity and factorial structure of a modified version of the Preschool Anxiety Scale (Spence, Rapee, McDonald, & Ingram, 2001). The measure was completed by 764 mothers and 418 fathers of children aged 3 to 5 years. After removing, two items tapping obsessive compulsive symptoms, confirmatory factor analysis showed that a four-factor model (social anxiety, generalized anxiety, separation anxiety, specific fears) all loading on a higher order "anxiety" factor, provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
149
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(155 citation statements)
references
References 37 publications
5
149
0
1
Order By: Relevance
“…Several studies have confirmed that anxiety symptoms in preschoolers tend to cluster into the specific categories above and support the use of these different diagnoses in preschoolers rather than one non-specific “anxiety disorder” diagnosis 15,91,92 . Notably, Post-Traumatic Stress Disorder (PTSD) and Obsessive-Compulsive Disorder (OCD) are no longer classified as anxiety disorders and are not considered here.…”
Section: Assessment Of Preschool Anxiety Disordersmentioning
confidence: 88%
“…Several studies have confirmed that anxiety symptoms in preschoolers tend to cluster into the specific categories above and support the use of these different diagnoses in preschoolers rather than one non-specific “anxiety disorder” diagnosis 15,91,92 . Notably, Post-Traumatic Stress Disorder (PTSD) and Obsessive-Compulsive Disorder (OCD) are no longer classified as anxiety disorders and are not considered here.…”
Section: Assessment Of Preschool Anxiety Disordersmentioning
confidence: 88%
“…First, anxiety disorders are among the most prevalent psychiatric disorders in young children (Edwards, Rapee, Kennedy, & Spence, 2010;Egger & Angold, 2006) and have the potential to cause significant developmental disruption (McLoone, Hudson, & Rapee, 2006); therefore, enhancing our understanding of risk and protective factors is critical. Second, the prevention of early childhood anxiety represents a significantly neglected area of research, with limited attention to the effectiveness of child-based early intervention and prevention programmes.…”
Section: Cbt Child-and Parent-based Interventionsmentioning
confidence: 99%
“…The prevalence of anxiety disorders in a community sample of preschool-aged children (2 -5 years) has been reported as 9.5% (Edwards, Rapee, Kennedy, & Spence, 2010;Egger & Angold, 2006), with up to 28.8% of children developing an anxiety disorder during their lifetime (Kessler et al, 2005;Merikangas et al, 2010). If untreated, anxiety has the potential to cause significant disruption to a child's developmental trajectory due to the chronic course and low rates of remission (McLoone, Hudson, & Rapee, 2006).…”
mentioning
confidence: 99%
“…apresenta um conjunto de sintomas bem especificados que devem ser respondidos pelos progenitores de acordo com a frequência da sua presença numa escala de 4 pontos que varia entre "nunca" e "sempre". Os itens, consistentes com as categorias da DSM-IV, foram selecionados por peritos no tema tendo em conta a literatura, medidas de diagnóstico internacional e entrevistas clínicas (Edwards, Rapee, Kennedy & Spence, 2010). A validação original do instrumento (Spence at al, 2001) foi administrada a crianças entre os 3 e os 5 anos de idade e está organizada em cinco categorias de diagnóstico: Perturbação de ansiedade generalizada (PAG), perturbação de ansiedade social (PAS), ansiedade de separação (AS), perturbação obsessivo-compulsiva (POC) e medo de dano físico (MDF) as quais estão associadas num fator "ansiedade" superordenado responsável pelo covariância entre os fatores sugerindo que, em idades precoces, a ansiedade poderá ser um constructo unitário.…”
Section: Avaliação Do Medo Na Idade Pré-escolarunclassified